Intercultural Adaptation and Cultural Dominance between Engganese and Kaamay - Endang Saputra; Intan Permata Sari; Dhanurseto Hadiprashada (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Engganese are a community that adapts well to change. They can anticipate social, political, and economic changes around them by using Engganese customs as a guide. This article aims to describe the adaptation strategies and intercultural communication between the Engganese and migrants (kaamay) to reduce the potential conflict. This study integrates Young Yun Kim’s Integrative Communication Theory to analyze the process of migrants' deculturation, and Larry Samovar’s concept of High-Context Communication to explain the power of customary rules as a singular guide to life. This study employs a qualitative method through observation and in-depth interviews with Engganese community leaders and migrants. The findings reveal that the Engganese engage in three forms of adaptation: 1) forming kaamay as a form of cultural strategy; 2) using Bahasa as a tool for communication with kaamay; and 3) engaging in intermarriage for social integration. These findings indicate that the Engganese, as a minority group, have successfully demonstrated cultural dominance by preserving Engganese customs and compelling the Kaamay to relinquish their cultural identities and conform to Engganese customs.